The Design, Implementation, and Evaluation of a Health-Themed Residential Learning Community for Undergraduate Students. Issue 4 (July 2020) - Lederer, Alyssa M.; Tims, M. Scott; Czachowski, Alicia K.; Williams-Aghimien, Sonia E.; Pinto, Celeste A.
College students face significant health concerns. In recent years, there has been an emergence of health-related residential learning communities (RLCs) at institutions of higher education, which endeavor to improve students' academic and health outcomes by offering a communal living environment and programming. However, there is negligible literature describing health-related RLCs as a health promotion intervention, the kind of experience residents have, or the impact that health-related RLCs have on student outcomes. To begin to fill this gap, this article describes a health-themed RLC named HealthWave that was created at a private Southern university and the diverse stakeholders involved. It also summarizes results from a multimethod evaluation that included focus groups, an experience survey, and a quasi-experimental study with non-HealthWave students in the same residence hall as the comparison group. HealthWave was a feasible intervention to implement and residents provided very positive feedback about their experience, although the impact of HealthWave on students' health behavior is unclear. Lessons learned from implementing and evaluating HealthWave are shared in order to inform health promotion professionals' future programmatic and evaluation efforts.